Integrated and partial process of xylitol and bioethanol production from oil palm empty fruit bunches - Efri Mardawati; Budi Mandra Harahap; Emilda Ayu Febrianti; Agus Try Hartono; Natasha Putri Siahaan; Anting Wulandari; Silvia Yudiastuti; Sri Suhartini; Kasbawati Kasbawati (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Oil palm empty fruit bunches (OPEFBs) are highly abundant in Indonesia and have been highlighted as a potential feedstock for bioethanol and xylitol production. However, the efficacy of the fermentation technology to convert OPEFBs to bioethanol and xylitol, either in partial (i.e. mono-production) or integrated (i.e. co-production) process, still needs further improvement. This study aimed to evaluate the partial and integrated process for xylitol and bioethanol production from OPEFBs.  In the integrated process, the remaining solid residues after xylitol extraction are used as feedstock for bioethanol due to their high cellulose compounds. This solid residue is more susceptible to be degraded by cellulase enzymes into glucose and further transformed into bioethanol. In the partial process of xylitol production, xylanase enzyme was used to hydrolyze xylan into xylose, which was then converted into xylitol using Debaryomyces hansenii. While in the partial process of bioethanol production, the hydrolysis of cellulose in the OPEFB into glucose was carried out using cellulase enzymes, followed by fermentation using Saccharomyces cerevisiae. The results show that the partial process produced xylitol yield (Yp/s) of 0.10 g-xylitol/g-xylose, while bioethanol at yield (Yp/s) of 0.32 g-bioethanol/g-glucose, respectively. The integrated process generates xylitol yield (Yp/s)of 0.298 g-xylitol/g-xylose, with bioethanol yield from the remaining solid at 0.051 g-bioethanol/g-OPEFB (or 0.078 g-bioethanol/g-glucose). These findings, therefore, confirmed that the integrated process of xylitol with bioethanol production might offer higher efficacy of OPEFB utilization into high value-added products.